Resumption to swimming post COVID 19 lockdown - Ramya, G.; Guru, C. S.; Banodhe, G. K.; Dominic, D.; Sharma, H. B.. (Journal of Clinical and Diagnostic Research, 2021)
COVID-19 pandemic has severely affected sports worldwide Usual practice can`t be done due to high viral transmission, yet prolonged inactivity leads to detraining and deconditioning and threatens ending of sporting career Depending on the present guidelines of the government, a safe and evidence based gradual resumption of training and sports is essential The cardiorespiratoryneuromuscular system involvement among others in COVID-19 directly affects exercise-sports performance and health, and the possibility of sub-clinical transmission poses immense challenge Like other games, swimming is also heavily affected Although COVID-19 is transmitted by droplets, the prolonged presence of virus in the air currents, commonly-touched surfaces and in stool of those infected should be kept in mind Importance of hand hygiene, cough and sneeze etiquette, social distancing, use of mask while not exercising hard, other good public hygiene practices, staying home if sick, frequent cleaning and disinfection of pool and frequently touched surfaces, early detection, isolation and adequate treatment for the positive cases and strictly following government guideline should be compulsory Awareness program and continued education for athletes, parents, coaches, support staff and other management team should be done This review is intended to understand the course of COVID-19 and to formulate guidelines for resumption of swimming in India, based on recommendations by various organisations like WHO, CDC etc The aim being to act as a key support for safely resuming swimming yet reducing the risk of COVID-19 infection